Sustainable Ecotourism Development Strategy for Mina-Minanga Beach in North Buton Regency - La Hatani; La Ode Anto; Riski Amalia Madi; Nurul Ittaqullah (Apollo: Journal of Tourism and Business, 2024)
This study explores the sustainable ecotourism development strategies for Mina-Minanga Beach in North Buton Regency, Southeast Sulawesi. Utilizing SWOT (Strengths, Weaknesses, Opportunities, Threats) and ANP (Analytic Network Process) analyses, the research identifies key factors influencing ecotourism management and prioritizes strategic actions to enhance sustainability. The findings highlight the beach's stunning natural landscapes, including coral reefs and mangrove forests, and the strong community support for ecotourism as significant strengths. However, challenges such as poor waste management, limited infrastructure, and insufficient local tourism management knowledge must be addressed. Opportunities lie in the beach's strategic location and the growing global interest in ecotourism, which can be leveraged to develop unique cultural, educational, and adventure tourism products. Key strategies recommended include activating beach cleanliness programs, implementing sustainable conservation practices, and building disaster-resilient infrastructure. Additionally, ongoing training and education for local communities are crucial to ensure their active participation and capacity to manage tourism effectively. This research contributes to a comprehensive framework for developing sustainable ecotourism at Mina-Minanga Beach, aiming to balance environmental conservation with economic growth and community empowerment. The insights gained can inform policy-making and strategic planning, positioning North Buton Regency as a leading ecotourism destination in Indonesia while preserving its rich natural_and_cultural_heritage